Screening anti‐gout compounds from Phellinus igniarius by ultrafiltration liquid chromatography mass spectrometry based on evaluation of an in vitro method combined with enzymatic reaction. Issue 15 (10th June 2021) - Wang, Jing; Song, Jiling; Zhang, Yong; Gou, Shasha; Shi, Bingqing; Shi, Dongfang; Zheng, Meizhu; Yu, Min; Liu, Chun‐ming
Abstract: In the present study, the anti‐inflammation effect of Phellinus igniarius extract was detected on an in vitro model of RAW 264.7 cells stimulated using sodium urate. In this cell model, the content changes of inflammatory cytokines, intercellular adhesion molecule‐1, and interleukin‐1 beta, in cell culture supernatants were detected using an enzyme‐linked immunosorbent assay. The xanthine oxidase inhibitory activity of P. igniarius extracts was determined using a microplate reader. Furthermore, in order to identify the active compounds of P. igniarius, ultrafiltration liquid chromatography mass spectrometry was utilized to screen xanthine oxidase inhibitors from the extract. Our results showed that in the presence of P. igniarius extract, the expressions of interleukin‐1 beta and intercellular adhesion molecule‐1 decreased ( p < 0.01 and p < 0.05, respectively) compared to that in the control group. The extract effective inhibited the xanthine oxidase activity. Finally, seven compounds were screened and identified as potential xanthine oxidase inhibitors from P. igniarius . Taken together, these results demonstrate a potential anti‐inflammation bioactivity of P. igniarius in vitro, providing a basis for further in vivo research for the prevention and treatment of gout.